DETERMINAN BELANJA DAERAH DI KOTA LANGSA - Reza Maulana; Nasrul Kahfi Lubis; Meutia, Tuti (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This study was conducted with the aim of determining the effect of population variables, General Allocation Fund and Special Allocation Fund on regional spending in Langsa City from 2003 to 2017. The data used are population data from 2003 to 2017 obtained from the Langsa City Central Statistics Agency and data on General Allocation Fund, Special Allocation Fund and Regional Spending obtained from the Langsa City Regional Financial Management Agency from 2003 to 2017. The data analysis method used in this study is multiple linear regression equations, the hypothesis test used in this study is the partial test (t test), simultaneous test (F test) and determinant coefficient (R2). The results of the t-test show that the number of residents has a significant effect on regional spending in Langsa City, the results of the t-test show that the General Allocation Fund (DAU) has a significant effect on regional spending in Langsa City, and the results of the t-test show that the Special Allocation Fund (DAK) has a significant effect on regional spending in Langsa City. The results of the F-test show that the Number of Residents, General Allocation Fund (DAU) and Special Allocation Fund (DAK) have a simultaneous effect on regional spending in Langsa City and the value of the determination coefficient (R2) is obtained at 0.984 or 98.4% which is influenced by the Number of Residents, General Allocation Fund and Special Allocation Fund while the remaining 1.6% is influenced by variables not included in this study.